Distal arteriopathies: Pathology and treatment with vein graft - Danza, Rómulo; Arias, José; Pravia, Juan A; Chiossoni, Marta (Cirugía del Uruguay, 2021)
The authors discuss chronic arterial distal obstructions in the leg. There is a case of short venous graft of the anterior tibial to the pedia artery and a long one of the femoral to the posterior tibial and tibioperoneal trunk.